Influence of noninjecting and injecting drug use on mortality, retention in the cohort, and antiretroviral therapy, in participants in the Swiss HIV Cohort Study. Issue 3 (15th August 2014) - Weber, R; Huber, M; Battegay, M; Stähelin, C; Castro Batanjer, E; Calmy, A; Bregenzer, A; Bernasconi, E; Schoeni‐Affolter, F; Ledergerber, B; Swiss HIV Cohort Study
<x xml:space="preserve">Abstract</x> Objectives We studied the influence of noninjecting and injecting drug use on mortality, dropout rate, and the course of antiretroviral therapy (ART), in the Swiss HIV Cohort Study (SHCS). Methods Cohort participants, registered prior to April 2007 and with at least one drug use questionnaire completed until May 2013, were categorized according to their self‐reported drug use behaviour. The probabilities of death and dropout were separately analysed using multivariable competing risks proportional hazards regression models with mutual correction for the other endpoint. Furthermore, we describe the influence of drug use on the course of ART. Results A total of 6529 participants (including 31% women) were followed during 31 215 person‐years; 5.1% participants died; 10.5% were lost to follow‐up. Among persons with homosexual or heterosexual HIV transmission, noninjecting drug use was associated with higher all‐cause mortality [subhazard rate (SHR) 1.73; 95% confidence interval (CI) 1.07–2.83], compared with no drug use. Also, mortality was increased among former injecting drug users (IDUs) who reported noninjecting drug use (SHR 2.34; 95% CI 1.49–3.69). Noninjecting drug use was associated with higher dropout rates. The mean proportion of time with suppressed viral replication was 82.2% in all participants, irrespective of ART status, and 91.2% in those on ART. Drug use lowered adherence, and increased rates of ART change and ART interruptions. Virological failure on ART was more frequent in participants who reported concomitant drug injections while on opiate substitution, and in current IDUs, but not among noninjecting drug users. Conclusions Noninjecting drug use and injecting drug use are modifiable risks for death, and they lower retention in a cohort and complicate ART.